Marketing research : a practical approach - Kolb, Bonita M. (SAGE, 2008)
Essential to any student of the discipline, this book offers a comprehensive, applied approach to understanding and designing market research. Balancing the fundamental quantitative methodologies and theoretical structures with practical applications of qualitative techniques.